Identification of a Ninein (NIN) mutation in a family with spondyloepimetaphyseal dysplasia with joint laxity (leptodactylic type)-like phenotype - Grosch, Melanie; Gruener, Barbara; Spranger, Stephanie; Stuetz, Adrian M.; Rausch, Tobias; Korbel, Jan O.; Seelow, Dominik; Nuernberg, Peter; Sticht, Heinrich; Lausch, Ekkehart; Zabel, Bernhard; Winterpacht, Andreas; et al. (Matrix Biology, 2013)
Spondyloepimetaphyseal dysplasia with joint laxity-leptodactylic type (SEMDJL2) is an autosomal dominant skeletal dysplasia which is characterized by midface hypoplasia, short stature, joint laxity with dislocations, genua valga, progressive scoliosis, and slender fingers. Recently, heterozygous missense mutations in KIF22, a gene which encodes a member of the kinesin-like protein family, have been identified in sporadic as well as familial cases of SEMDJL2. In the present study homozygosity mapping and whole-exome sequencing were combined to analyze a consanguineous family with a phenotype resembling SEMDJL2. We identified homozygous missense mutations in the two nearby genes NIN (Ninein) and POLE2 (DNA polymerase epsilon subunit B) which segregate with the disease in the family and were not present in 500 healthy control individuals and in the 1094 control individuals contained within the 1000-genomes database. We present several lines of evidence that mutant Ninein is most likely causative for the SEMDJL2-like phenotype. The centrosomal protein NIN shows a functional relationship with KIF22 and other proteins associated with chromosome congression/movement, centrosomal function, and ciliogenesis, which have been associated with skeletal dysplasias. Moreover, compound heterozygous missense mutations at more N-terminal positions of Ninein have very recently been identified in a family with microcephalic primordial dwarfism. Together with the present report this strongly supports a fundamental role of Ninein in skeletal development.
EVALuna2:9192